Outlier and normality testing of the residuals from the Carreau-Yasuda model in fitting the rheological behavior of the non-Newtonian fluid TF2N - Shukor, Mohd Yunus (Hibiscus Publisher, 2021)
Non-Newtonian fluids include a variety of regularly encountered substances such as custard, honey, toothpaste, starch suspensions (including starch from corn starch), paint, blood, melted butter, and hairspray. For decades, scientists have investigated non-Newtonian fluid behavior and produced models to aid in the characterization of non-Newtonian fluid behavior. In addition to data interpolation and extrapolation, the outputs of these models may be utilized for material classification based on model parameters and aid with the simulation of computational fluid dynamics. The Carreau-Yasuda model fitted to the rheological behavior of the non-Newtonian fluid1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl) imide ([emim][TF2N]) was checked for its conformation to the normal distribution of its residual using the normality tests , which was found not to pass all of the test. After checking for the presence of an outlier using the Grubbs ‘test, no outlier was detected. The ROUT method was then applied to detect the presence of outliers and three outliers were found and removed. The normality checks performed on the cleaned residues gave acceptable results in terms of normality tests and visual conformation of the residual, Q-Q plot and overlaid normality curve to the histogram, indicating that the model is now appropriate for the data.